2013
DOI: 10.1111/sbr.12019
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of short-term efficacy between individual and group cognitive behavioral therapy for primary insomnia

Abstract: The purpose of this study was to compare the efficacy of individual and group cognitive behavioral therapy for insomnia (CBT-I) in outpatients with primary insomnia diagnosed by DSM-IV-TR. The participants were 20 individually treated (I-CBT-I) and 25 treated in a group therapy format (three to five patients per group) (G-CBT-I), which showed no significant difference regarding demographic variables between groups. The same components of CBT-I stimulus control therapy, sleep restriction therapy, cognitive ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The components of CBT may include stimulus control (limiting time in bed when unable to fall asleep), sleep hygiene education, and relaxation training (Perlis, Jungquist, Smith, & Posner, ). CBT has been found effective for insomnia in former studies (de Bruin, Oort, Bögels, & Meijer, ; Yamadera et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…The components of CBT may include stimulus control (limiting time in bed when unable to fall asleep), sleep hygiene education, and relaxation training (Perlis, Jungquist, Smith, & Posner, ). CBT has been found effective for insomnia in former studies (de Bruin, Oort, Bögels, & Meijer, ; Yamadera et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Participants had low baseline levels of psychosocial distress (e.g., catastrophizing, depression) and we studied group CBT, which has demonstrated efficacy, 33,40,55 resource-efficiency, and potential social benefits, but which may be less effective than individual CBT. 36,66 The results may not generalize to more distressed populations (e.g., pain clinic patients), which would have more room to improve on measures of maladaptive functioning and greater potential for treatments to differentially affect these measures, or to comparisons of MBSR with individual CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Note: * EA group versus EA/CBT group, P < 0.05; Δ CBT group versus EA/ CBT group, P < 0.05. [24,25]. Previous studies have confirmed that targeted corrections about sleep beliefs and attitudes can improve sleep quality [26].…”
Section: Baselinementioning
confidence: 95%